A NEW SPECTRUM DEVELOPMENT METHODOLOGY BASED ON PSEUDO DAMAGE RESERVING FOR ROAD LOAD SIMULATION TEST - ZHENG SongLin; ZHOU YaJie; FENG JinZhi; YU JiaWei (Jixie qiangdu)
Loading spectrum collected from proving ground contains large amounts of low-amplitude loads. For accelerating test,low-amplitude loads should be removed. Traditional spectrum compilation method generally based on stress or strain damage editing. However,obtaining stress or strain signal from engineering practice is difficult. Considering this problem,this paper proposed a new criterion to remove low-amplitude loads based on pseudo damage reserving. Taking a vehicle sub-frame fatigue test as an example,90% pseudo damage reserved spectrum is obtained by dealing with original load spectrum with this method.A comparison of accelerated load spectrum with original load spectrum was made in time,amplitude and frequency domains. It turned out that the accelerated load spectrum can be used for durability test instead of the original one. Finally,a bench test was conducted. The result shows the consistency of accelerated load spectrum and original load spectrum on the premise of saving durability test time. Also,the rationality of the load spectrum compilation method proposed in this paper was verified.